Il nuovo sistema di acquisizione e visualizzazione dei dati di Campo Magnetico Terrestre ... : The new system for data acquisition and visualisation of the Magnetic Field of the Earth ... - Bagiacchi, Paolo; Benedetti, Giovanni; Cafarella, Lili; Di Mauro, Domenico; Zirizzotti, Achille Emanuele (Istituto Nazionale di Geofisica e Vulcanologia (INGV), 2021)
For many years, INGV has been recording, sharing and analyzing data relating to the Earth’s magnetic field (CMT) from geomagnetic stations and observatories, placed on national territory and southern polar area. Besides, the Institute is a member of Intermagnet (http://www.intermagnet.org/), an international consortium of institutes that records and delivers each own magnetic field values collected at ground observatories. Data sent to Intermagnet can be freely visualized and downloaded from the scientific community interested in the topic. The observatories and monitoring stations managed by INGV are located 6 in Italy and 2 in Antarctica. Each station/observatory is composed of 2 similar and parallel acquisition systems to ensure continuity of the recording of the components and intensity of the magnetic field vector, as recommended by the IAGA (International Association of Geomagnetism and Aeronomy). Given the variety of models and types of instruments available at INGV, the unification of the acquisition ... : L’INGV da molti anni registra, analizza e distribuisce i dati di campo magnetico terrestre (CMT) provenienti da osservatori geomagnetici e stazioni temporanee dislocati sul territorio nazionale e in area polare sud [Cafarella et al., 2016]. Inoltre l’Istituto è membro del consorzio internazionale Intermagnet (http://www.intermagnet.org/), un consorzio di istituti ed enti scientifici che registrano e distribuiscono le proprie osservazioni del CMT. I dati inviati ad Intermagnet possono essere visualizzati e scaricati liberamente dalla comunità scientifica del settore. Gli osservatori e le stazioni di monitoraggio gestite dall’INGV sono ubicati 6 in Italia e 2 in Antartide. Ogni stazione/osservatorio è composta da 2 sistemi analoghi e paralleli di acquisizione per garantire la continuità della registrazione delle componenti e dell’intensità del vettore del campo magnetico, come raccomandato dalla IAGA (International Association of Geomagnetism and Aeronomy). Vista la varietà di modelli e tipologie di strumenti ...